Karakteristik Fisikokimia dan Sensori Susu Kacang Merah Stroberi dengan Perlakuan Rasio Kacang Merah dan Stroberi - Silitonga, Cintya Rodi Paskah; Wisaniyasa, Ni Wayan; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Red beans are legumes that can be utilized in making plant-based milk as an alternative to animal milk for people with lactose intolerance. Red bean milk are rich in nutrients but have a beany taste and a less preferred earthy aroma. Strawberries has a refreshing sweet and sour taste, distinctive fruit aroma, with high vitamin C content, so with addition of strawberries can be improved the sensory characteristics of red bean milk.. This experiment aims to analyze the effect of red beans and strawberries ratio on physicochemical and sensory characteristics and to get the right ratio of red bean strawberry milk with the best characteristics. This research was used a Completely Randomized Design with treatments of the ratio red bean and strawberry extract consisting of 6 levels, namely: 100:0, 95:5, 90:10, 85:15, 80:20, and 75:25, with 3 replications resulting in 18 experimental units. Data analyzed by analysis of variance, treatment that significantly affected (P<0,05) were analyzed by Duncan's Multiple Range Test. The results showed that the ratio of red bean to strawberry extract significantly affected total dissolved solids, viscosity, pH value, protein content, vitamin C content, antioxidant activity, hedonic color, aroma, texture, taste, overall acceptance and scoring color, aroma, taste. The ratio of 75% red bean extract and 25% strawberry extract produced milk with the best characteristics, with total dissolved solids of 14,00 %Brix, viscosity of 40,00 mPas, water content of 82,70%, pH value of 5,73, protein content of 1,19%, vitamin C of 24,37 mg/ml, and antioxidant activity of 69,54%, liked light pink color, liked aroma and taste distinctly strawberry, texture and overall acceptance liked by the panelists. Keywords: plant-based milk, red bean, strawberry